Experimental Investigation of Electrothermal Desorption of Steel Mill Gases from Activated Carbon. Issue 10 (16th June 2022) - Peters, Martin; Geitner, Christian; Verhoeven, Birte Friederike
Abstract: A bench‐scale electric swing adsorption plant has been used to investigate electrothermal desorption behavior by varying technically relevant factors like maximum electric power, purge gas flow and desorption temperature. The study has been planned by design of experiments using a central composite design. Different quality criteria have been defined to describe a macroscopic behavior of the desorption for process development. The results are used to fit models by multiple linear regression. For technically relevant quality criteria good correlating models could be found and can be used for accurate prediction of, e.g., the energy demand, purge gas total volume or desorption time. Abstract : The electrothermal desorption is investigated in a fixed‐bed system with granular activated carbon as adsorbent. For the investigation, factors and quality criteria with technical background are chosen to fit models to the experimental results. The behavior of the electric swing adsorption system can be predicted well with the regression models.